Como a perda da cobertura florestal afeta a abundância e as características corporais de espécies florestais que habitam paisagens urbanas amazônicas? Um estudo de caso com rola bostas - Bernardino, Glenda (Instituto Nacional de Pesquisas da Amazônia - INPA, 2023)
The loss of forest cover in urban landscapes alters the dynamics of spatial and food resources, challenging the maintenance of forest species, which may have their condition and suitability compromised. Dung beetles are sensitive to changes in vegetation structure and land use caused by human activities, processes that are intrinsically related to the establishment and development of cities. The aim of this study was to evaluate the effect of landscape structure on the abundance and morphological characteristics of two species of dung beetle (Dichotomius boreus and Dichotomius quadrilobatus) that inhabit forested areas in urbanized landscapes in the Amazon region. We carried out the study in 38 landscapes located in six urban regions in the central region of the Amazon. We evaluated the effect of landscape structure, at the site and city scales, on beetle abundance, individual body size, and relative horn length of males. At the local scale, landscapes with greater forest cover showed greater abundance of dung beetles, as well as greater lengths of D. boreus horns. Cities with a greater amount of forest cover had larger individuals than those with less forest cover. We conclude that forested areas in urban landscapes are a key habitat for the maintenance of dung beetle populations with a strong relationship between the amount of forest cover in the landscape. The maintenance of healthy and abundant populations of beetles in urban Amazonian landscapes guarantees the persistence of ecosystem services provided by these organisms in urban ecosystems.
Keywords: Crescimento urbano; Floresta tropical úmida; Scarabaeinae; urbanização